Lawrie's meat science - Lawrie, R. A. (CRC Press ; Woodhead Pub., 2006)
Lawrie's Meat Science has established itself as a standard work for both students and professionals in the meat industry. Its basic theme remains the central importance of biochemistry in understanding the production, storage, processing and eating quality of meat. At a time when so much controversy surrounds meat production and nutrition, Lawrie's meat science, written by Lawrie in collaboration with Ledward, provides a clear guide which takes the reader from the growth and development of meat animals, through the conversion of muscle to meat, to the point of consumption. The seventh edition includes details of significant advances in meat science which have taken place in recent years, especially in areas of eating quality of meat and meat biochemistry. A standard reference for the meat industryDiscusses the importance of biochemistry in production, storage and processing of meatIncludes significant advances in meat and meat biochemistry.
Previous ed.: published as Meat science. Oxford : Pergamon, 1991.
Keywords: Meat.; elektronické knihy; electronic books